Plasma concentrations resulting from continuous infusion of meropenem in a community-based outpatient program: A case series. (4th December 2020) - Legg, Amy; Halford, Melanie; McCarthy, Kate
Abstract: Purpose: Traditionally meropenem has been considered too unstable in solution for continuous infusion. However, in the era of increasing antimicrobial resistance, use of meropenem is becoming more frequently required, and the ability to facilitate its administration via community-based programs would be beneficial. There are some reassuring data about meropenem stability in solution, but data about actual drug exposure in patients and subsequent clinical outcomes are lacking. Summary: Here we present a case series of 4 patients at a single tertiary center who received meropenem via continuous infusion coordinated through an outpatient parenteral antimicrobial treatment (OPAT) program. We provide plasma drug concentrations achieved and report on the patients' clinical progress. All patients achieved drug concentrations of at least 2 times the minimum inhibitory concentration (MIC) while receiving meropenem via continuous infusion and had resolution of their infectious complications. No adverse effects of meropenem continuous infusion were noted. Conclusion: Meropenem continuous infusion along with therapeutic drug monitoring was used successfully in a community-based program. Due to interpatient pharmacokinetic variability, we consider meropenem concentration monitoring compulsory during continuous-infusion meropenem therapy.